When Intervention Meets Organisation, a Qualitative Study of Motivation and Barriers to Physical Exercise at the Workplace - Bredahl, Thomas Viskum Gjelstrup (ScientificWorldJournal, 2015)
Objective. To provide a comprehensive understanding of the motivational factors and barriers that are important for compliance with high-intensity workplace physical exercise that is aimed at reducing musculoskeletal disorders. Method. The present study, which used semideductive, thematic, and structured in-depth interviews, was nested in a 20-week cluster randomised controlled trial among office workers. Interviews were conducted with 18 informants with diverse fields of sedentary office work who participated in strength training at the workplace for 20 minutes, three times per week. Organisational, implementational, and individual motives and barriers were explored. Results & Discussion. The results show that attention should be given to the interaction between the management, the employees, and the intervention, as the main barrier to compliance was the internal working culture. The results emphasised the need for a clear connection between the management's implementational intentions and the actual implementation. The results emphasise the importance of ensuring the legitimacy of the intervention among managers, participants, and colleagues. Moreover, it is important to centrally organise, structure, and ensure flexibility in the working day to free time for participants to attend the intervention. Recommendations from this study suggest that a thorough intervention mapping process should be performed to analyse organisational and implementational factors before initiating workplace physical exercise training.